Effect of ischaemic preconditioning on recurrence of hepatocellular carcinoma in an experimental model of liver steatosis. Issue 4 (18th February 2016) - Orci, L A; Lacotte, S; Oldani, G; Slits, F; De Vito, C; Crowe, L A; Rubbia-Brandt, L; Vallée, J-P; Morel, P; Toso, C
Abstract: Background: Livers with parenchymal abnormalities tolerate ischaemia–reperfusion (IR) injury poorly. IR injury is a risk factor for hepatocellular carcinoma (HCC) recurrence. This study assessed the link between liver parenchymal abnormalities and HCC recurrence, and evaluated the protective effect of ischaemic preconditioning. Methods: C57BL/6 mice were fed a choline-deficient diet for 6 and 12 weeks, or standard chow. Hepatic IR and ischaemic preconditioning were achieved by clamping liver blood inflow. Hepa 1–6 HCC cells were inoculated through the spleen. Thereafter, tumour burden, serum α-fetoprotein and cancer cell aggressiveness were compared among groups. Results: Hepatocellular damage and expression of inflammatory genes (encoding interleukin 6, tumour necrosis factor α, hypoxia inducible factor 1α and E-selectin) were exacerbated after IR injury in mice with severe steatosis. Compared with control livers or those with minimal steatosis, livers exposed to a prolonged choline-deficient diet developed larger tumour nodules and had higher serum α-fetoprotein levels. Non-ischaemic liver lobes from mice with steatosis were not protected from accelerated tumour growth mediated by IR injury. This remote effect was linked to promotion of the aggressiveness of HCC cells. Ischaemic preconditioning before IR injury reduced the tumour burden to the level of that in non-ischaemic steatotic controls. This protective effect was associated with decreased cancer cell motility. Conclusion: Livers with steatosis tolerated IR poorly, contributing to more severe HCC recurrence patterns in mice with increasingly severe steatosis. IR injury also had a remote effect on cancer cell aggressiveness. Ischaemic preconditioning before IR injury reduced tumour load and serum α-fetoprotein levels. Surgical relevance Liver ischaemia–reperfusion (IR) injury is associated with organ dysfunction and surgical morbidity. Livers with steatosis tolerate IR injury poorly in the setting of both liver resection and liver transplantation. Ischaemic preconditioning is a simple method to mitigate IR injury. This study shows that ischaemic preconditioning of mouse livers with steatosis reduces ischaemia-mediated tumour growth acceleration. Liver parenchymal abnormalities such as warm IR injury and liver steatosis should be taken into account to predict accurately the risk of liver cancer recurrence after surgical management. Ischaemic preconditioning strategies may hold therapeutic potential not only to mitigate surgical morbidity but also to reduce postoperative recurrence of liver cancer. Abstract : Reduces risk